Proceedings of 2015 2nd national foundationfor science and technology development conference on onformation and computer science - Nafosted (National foundation for science and technology development) (Ho Chi Minh city, 2015)
This volume comprises the proceeding of the 2nd NICS conference. There are consists of 4 main tracks: Foundations of computer science, Software engineering and information systems, Computational intelligence and communication and networking.